ESTRUCTURACIÓN DEL PROCESO DE RECEPCIÓN, ASIGNACIÓN Y EVACUACIÓN DE REQUERIMIENTOS DE TRÁMITES JURÍDICOS DE LOS CLIENTES DE LA EMPRESA VELASCO ORDÓÑEZ S.A.S. MEDIANTE LA METODOLOGÍA BUSINESS PROCESS MANAGEMENT (BPM) - LUISA GÁMEZ CARRACEDO; ÉVER ÁNGEL FUENTES ROJAS (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Velasco Ordóñez S.A.S. is a company dedicated to legal advice, with which its main workforce is made up of lawyers,specializing in Intellectual Property and Market Law. In order to make better use of their time in order to provide timelyattention to all the requirements received by customer parties, the project was developed based on the guidelines of theBPM methodology, finally getting the presentation of three possible scenarios whose simulations and structuring yieldednew possible availabilities up to 76%, thus benefiting customer response times and company productivity levels.